1972
DOI: 10.1126/science.177.4044.166
|View full text |Cite
|
Sign up to set email alerts
|

Around-the-World Atomic Clocks: Predicted Relativistic Time Gains

Abstract: During October 1971, four cesium beam atomic clocks were flown on regularly scheduled commercial jet flights around the world twice, once eastward and once westward, to test Einstein's theory of relativity with macroscopic clocks. From the actual flight paths of each trip, the theory predicts that the flying clocks, compared with reference clocks at the U.S. Naval Observatory, should have lost 40 +/- 23 nanoseconds during the eastward trip, and should have gained 275 +/- 21 nanoseconds during the westward trip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
224
1
3

Year Published

1984
1984
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 432 publications
(252 citation statements)
references
References 8 publications
14
224
1
3
Order By: Relevance
“…According to the rules of LT the observer in A can regard his frame at rest and B as a moving frame. The Hafele-Keating experiments [11] however show a slower running clock in its own system. In this case, A would measure a faster running clock in B, which is inconsistent with the STR.…”
Section: Does An Observed Clock Run Faster?mentioning
confidence: 99%
See 1 more Smart Citation
“…According to the rules of LT the observer in A can regard his frame at rest and B as a moving frame. The Hafele-Keating experiments [11] however show a slower running clock in its own system. In this case, A would measure a faster running clock in B, which is inconsistent with the STR.…”
Section: Does An Observed Clock Run Faster?mentioning
confidence: 99%
“…Because of isotropic light emission, a laser pulse (in north-south direction) should hit a detector positioned exactly opposite in its own reference frame A [9][10][11]. Is this valid?…”
Section: Does the Light Clock Really Work?mentioning
confidence: 99%
“…The eastbound traveler lost 59 nanoseconds, while the one transported westward gained 273 nanoseconds. 80 Other experiments with cosmic-ray muons (particles that enter into the Earth's atmosphere from outer space) showed that their lifespan before decaying was noticeably increased. Scientists interpreted the particles' prolonged life as due to time dilation effects arising from traveling at speeds close to that of light.…”
Section: Rise and Fallmentioning
confidence: 99%
“…It was entirely conventional: "the time of a distant event can be chosen as we wish." 80 The historian of science looked closely at the exact timeline of Einstein's work. He noticed that the physicist had first defined a particular procedure of synchronizing clocks at a distance, which then resulted in constant measurements for the speed of light, not the other way around:…”
Section: Herbert Dingle and The History Of Sciencementioning
confidence: 99%
“…Naval Observatory performed an experiment to test time dilation in 1971, (Hafele and Keating 1972). Airline flights around the world in opposite directions carried four Cs atomic beam clocks.…”
Section: Time Dilation Testmentioning
confidence: 99%